Bibliometric Analysis of Institutional Theory Research - Baharom, Zulkiffly; Abdullah, Khairul Hafezad (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Institutional Theory is essential to understand organizational dynamics and social impacts on business conduct. This research performs a bibliometric analysis of the Institutional Theory literature using Scopus data processed through ScientoPy and VOSviewer. The results indicate a substantial increase in academic production in the last sixty years, especially since the early 2000s. Major publication sites include the Journal of Management Inquiry and the Journal of Management Studies. Notable topics include institutional theory, logic, corporate social responsibility, and sustainability. The work of Geels (2004) on sociotechnical systems is the most referenced. The United States ranks first in research contributions, followed by the United Kingdom and Canada. The study highlights the progressive adaptation of Institutional Theory to modern challenges, indicating the need for responsiveness to evolving organizational and social contexts. Future research should focus on the influence of Institutional Theory on sustainability, its facilitation of organizational transformation, and its applicability in diverse cultural and economic settings. These findings offer a key framework for researchers, policymakers, and practitioners to deepen their exploration of Institutional Theory and its relevance to organizational behavior and social impacts on business activities. This analysis provides significant insights to enhance theoretical frameworks and practical implementations of Institutional Theory in diverse organizational settings.